2017
DOI: 10.2196/jmir.7116
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management Support Using a Digital Health System Compared With Usual Care for Chronic Obstructive Pulmonary Disease: Randomized Controlled Trial

Abstract: BackgroundWe conducted a randomized controlled trial of a digital health system supporting clinical care through monitoring and self-management support in community-based patients with moderate to very severe chronic obstructive pulmonary disease (COPD).ObjectiveThe aim of this study was to determine the efficacy of a fully automated Internet-linked, tablet computer-based system of monitoring and self-management support (EDGE‚ sElf-management anD support proGrammE) in improving quality of life and clinical out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
140
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(146 citation statements)
references
References 52 publications
3
140
1
2
Order By: Relevance
“…All 13 trials [13][14][15][16][17][18][19][20][21][22][23][24] were published after 2008, with most (12 of 13) published since 2011. Trials were conducted in a number of countries and settings; however, most were in the Netherlands [17][18][19][20] or the United Kingdom 13,16,22,23 . Five trials 14,17,18,23,25 included fewer than 50 participants and the largest number of participants was 343 21 .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…All 13 trials [13][14][15][16][17][18][19][20][21][22][23][24] were published after 2008, with most (12 of 13) published since 2011. Trials were conducted in a number of countries and settings; however, most were in the Netherlands [17][18][19][20] or the United Kingdom 13,16,22,23 . Five trials 14,17,18,23,25 included fewer than 50 participants and the largest number of participants was 343 21 .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Baseline measures of lung function were identified in nine trials [13][14][15][16][17][18]20,21,25 . Study duration varied from 2 weeks 23 to 12 months 15,16,20,22 .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were recruited as part of a clinical trial (including pilot trial) (Farmer et al, 2017) evaluating the effectiveness of a digital health intervention supporting self-management in COPD. A qualitative, interview based study was conducted to explore participants' understanding and experience of living with and managing their condition at home, and how such an intervention might influence their self-management.…”
Section: Methodsmentioning
confidence: 99%
“…Velardo et al (2017) found a digital self-management health intervention led to higher compliance rates with the treatments and encouraged clinicians to be more engaged with monitoring patient outcomes. Farmer et al (2017) found that a similar intervention had no significant impact on condition-specific outcomes, but they did observe significant improvements in general health and significant reductions in the number of visits to practice nurses and general practitioners.…”
Section: Evidence On Impact From Related Interventionsmentioning
confidence: 95%